Virtual Laboratory-Based Physics Learning "PhET Simulation" to Improve Student Learning Activities - Dedi Holden Simbolon; Eka Kartika Silalahi (Jurnal Ilmiah Sekolah Dasar, 2023)
The rapid development of information technology in the digital era must be utilized optimally to improve the quality of learning Physics. The use of virtual laboratories can replace real laboratories as a means of proving theories, laws, and concepts of physics. This study aims to analyze the use of virtual media in the form of PhET simulation as an alternative to real experiments (reels). This type of research is an experiment) by providing treatment in the form of learning. The research subjects were Quality University students divided into 2 classes, namely the experimental class (2A23), totaling 32 students, and the control class (2B22), consisting of 33 students. Data collection techniques used research instruments, namely learning achievement tests and observations. Hypothesis testing in this study used a 2-way analysis of variance (Two Way Anova) on the univariance General Linear Model (GLM) with the SPSS 21 program. From the results of the study, there was a significant difference between the learning outcomes of Science Physics and the level of student activity in class compared to classes taught using a conventional method, so there is a significant interaction between learning methods and activity levels on student learning outcomes in Science Physics. It was concluded that using virtual laboratory learning methods based on PhET simulation, especially on fluid material, affected student learning outcomes.